Improving Toilet Hygiene and Handwashing Practices During and Post-COVID-19 Pandemic in Indonesian Schools - Afkar, Rythia; Kumala, Citra; Nomura, Shinsaku (World Bank, Washington, DC, 2021)
This policy note examines a rapid situation analysis of water, sanitation, and hygiene (WASH) facilities in Indonesian schools using quantitative and qualitative data, including a review of relevant regulations. It discusses policy implications related to the COVID-19 (coronavirus) pandemic response and its implications for achieving universal access to basic WASH facilities in schools by 2030, under the Sustainable Development Goals. It is found that 8 percent of MoECRT schools and 20 percent of MoRA primary schools have no functional toilets for students. The average number of toilets, 58 students to 1 toilet in primary schools, is not up to the international standards of 25:1 ratio. Twenty-two percent of MoECRT schools have no access to water and 47 percent reported no soap nor running water. The policy note also identifies 4 areas of policy gaps and corresponding recommendations to respond to the current situation and its causes.